ChemInform Abstract: One‐Step Synthesis of Isocoumarins and 3‐Benzylidenephthalides via Ligandless Pd‐Catalyzed Oxidative Coupling of Benzoic Acids and Vinylarenes. Issue 33 (25th July 2013) - Nandi, Debkumar; Ghosh, Debalina; Chen, Shih‐Ji; Kuo, Bing‐Chiuan; Wang, Nancy M.; Lee, Hon Man
Abstract Different benzoic acids containing electron‐drawing groups can be converted into the corresponding coumarines or phtalides via the simple title reaction.